Factors Affecting Teachers’ Turnover in Private Schools of Karachi - Ruby Naureen , Rozina Sewani, (PJE, 2023)
This study was done to examine the factors influencing teacher turnover in Karachi's private schools. The high teacher turnover rate in Karachi's private schools poses a hurdle to student performance and educational growth. In addition, due to the high teacher turnover, the educational process is slowing down, which has a negative impact on student productivity.